The dog who wouldn't be - Mowat, Farley (Bantam, 1981)
Farely Mowat's best loved book tells the splendidly entertaining story of his boyhood on the Canadian prairies. Mutt's pedigree was uncertain, but his madness was indisputable. He climbed trees and ladders, rode passenger in an open car wearing goggles and displaying hunting skills that bordered on sheer genius. He was a marvelous dog, worthy of an unusual boy growing up a raw, untamed wilderness.